Creep compaction behavior of 3D carbon interlock fabrics with lubrication and temperature. (July 2016) - Renaud, Joffrey; Vernet, Nicolas; Ruiz, Edu; Lebel, Louis Laberge
Abstract: This study aims at understanding and improving the compaction of 3D carbon interlock fabrics with water lubrication, high temperature and a combination of them. The creep compaction behavior was characterized in a mechanical testing machine under different lubrication and temperature conditions. Three different interlock fabrics were studied at high temperature in order to assess the influence of the weaving pattern on the creep compaction behavior. Finally, an experimental study was carried out to point the impact of fiber sizing on the creep compaction behavior and its evolution with temperature. The results of this work demonstrate the strong impact of temperature and lubrication on the compaction ability of 3D interlock fabrics and its link to the fiber sizing.